2013
DOI: 10.1519/jsc.0b013e3182815995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isometric and Dynamic Postactivation Potentiation Protocols on Maximal Sprint Performance

Abstract: This study examined the effects of 3 types of postactivation potentiation (PAP) protocols (single-joint isometric, multijoint isometric, and multijoint dynamic) on subsequent 10-m, 20-m and 30-m sprint performance in 12 well-trained male track athletes (mean ± SD age = 22.4 ± 3.2 years). The subjects performed 4 protocols in a randomized order on different days as follows: control (4 minutes of passive rest), maximum voluntary isometric knee extension (3 repetitions of 3-second isometric knee extension), maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 20 publications
4
72
1
6
Order By: Relevance
“…When recovery periods were individualized in professional rugby players, Bevan et al [19] found 0-5 m and 0-10 m sprint times were potentiated by 3 back squats performed with 91% of 1RM. In opposition to these findings, 30-m sprint times did not improve 4 min after performing a 3RM back squat in well-trained male and female track and field athletes [20]. A 3RM back squat also did not lead to improvements in 0-5 m [10], 0-10 m [10,18], or 0-30 m sprint times [18] in strength-trained collegiate American football or rugby players.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…When recovery periods were individualized in professional rugby players, Bevan et al [19] found 0-5 m and 0-10 m sprint times were potentiated by 3 back squats performed with 91% of 1RM. In opposition to these findings, 30-m sprint times did not improve 4 min after performing a 3RM back squat in well-trained male and female track and field athletes [20]. A 3RM back squat also did not lead to improvements in 0-5 m [10], 0-10 m [10,18], or 0-30 m sprint times [18] in strength-trained collegiate American football or rugby players.…”
Section: Introductionmentioning
confidence: 60%
“…For example, only Bevan et al [19] illustrated that 10-m sprint performance can be potentiated by a strength exercise. Numerous other studies have illustrated that speed over distances less than 20 m were not potentiated by a strength-based conditioning activity [10,15,16,18,20,21]. Yetter and Moir [16] stated that an exercise such as a back squat may not provide a movement-specific stimulation to the muscles required for sprint acceleration due to the different mechanical demands of acceleration versus maximal velocity sprinting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Till and Cook (2009) state in their study that there is no significant difference in sprint and vertical jump of potential practices after activity. Lim & Kong (2013), report in the study performed in 4 different days that there is no improvement in short-range sprint performance after PAP protocols and four-minute-rest period with single-articulated or multi-articulated irrespective of isometric or dynamics. Vanderka et al (2016), show in their study that there is no significant difference in the sprint time for athletes and footballers after jump squat, and the sprint time is negatively affected.…”
Section: Discussionmentioning
confidence: 95%
“…All of the studies evaluated males aged 16 to 25 years. The studies presented data of athletes from sports of collective modality (5-7, 9, 13, 22, 28-34), athleticism (21,35), and resistance trained subjects (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…However, some controversial results are observed, with some studies indicating no significant improvements on sprint performance (5)(6)(7)(8)(9). Many factors such as muscle fiber type (10), training experience (11), gender (12) and muscle strength level (13) can influence the individual responsiveness to PAP.…”
Section: Introductionmentioning
confidence: 99%